Unraveling the Interplay Between Fixed Income and Credit Markets - Kurni, Miradita (Advances in Economics & Financial Studies, 2023)
This study examines the interplay between fixed income and credit markets, aiming to elucidate their dynamics and implications for market participants. Utilizing a comprehensive research design, the study analyzes the influence of interest rates, credit spreads, market liquidity, and regulatory frameworks on market behavior and participant decision-making processes. Findings indicate that fluctuations in interest rates significantly affect investor sentiment, asset valuations, and risk perceptions, while credit spreads play a crucial rsole in shaping credit market dynamics. Moreover, market liquidity emerges as a key determinant of trading efficiency and price discovery processes, with regulatory interventions exerting profound effects on participant behavior and market stability. These findings underscore the complex nature of financial market interactions and highlight the importance of a multifaceted approach in understanding and navigating these interconnected markets. The implications of these findings extend to policymakers, investors, and researchers, emphasizing the need for adaptive strategies to address evolving market conditions and regulatory environments, ultimately enhancing market efficiency and safeguarding investor interests.